Rates and Determinants of Progression to Graft Failure in Kidney Allograft Recipients With De Novo Donor‐Specific Antibody. Issue 11 (10th June 2015) - Wiebe, C.; Gibson, I. W.; Blydt‐Hansen, T. D.; Pochinco, D.; Birk, P. E.; Ho, J.; Karpinski, M.; Goldberg, A.; Storsley, L.; Rush, D. N.; Nickerson, P. W.
<x xml:space="preserve">Abstract</x> Understanding rates and determinants of clinical pathologic progression for recipients with de novo donor‐specific antibody (dnDSA), especially subclinical dnDSA, may identify surrogate endpoints and inform clinical trial design. A consecutive cohort of 508 renal transplant recipients (n = 64 with dnDSA) was studied. Recipients (n = 388) without dnDSA or dysfunction had an eGFR decline of −0.65 mL/min/1.73 m2/year. In recipients with dnDSA, the rate eGFR decline was significantly increased prior to dnDSA onset (−2.89 vs. −0.65 mL/min/1.73 m2/year, p < 0.0001) and accelerated post‐dnDSA (−3.63 vs. −2.89 mL/min/1.73 m2/year, p < 0.0001), suggesting that dnDSA is both a marker and contributor to ongoing alloimmunity. Time to 50% post‐dnDSA graft loss was longer in recipients with subclinical versus a clinical dnDSA phenotype (8.3 vs. 3.3 years, p < 0.0001). Analysis of 1091 allograft biopsies found that dnDSA and time independently predicted chronic glomerulopathy (cg), but not interstitial fibrosis and tubular atrophy (IFTA). Early T cell–mediated rejection, nonadherence, and time were multivariate predictors of IFTA. Independent risk factors for post‐dnDSA graft survival available prior to, or at the time of, dnDSA detection were delayed graft function, nonadherence, dnDSA mean fluorescence intensity sum score, tubulitis, and cg. Ultimately, dnDSA is part of a continuum of mixed alloimmune‐mediated injury, which requires solutions targeting T and B cells.